Penguatan Media dan Komunikasi melalui Optimalisasi Publikasi di Yayasan Rekat Peduli Indonesia - Adriel Bigael Lois Saiya; Andi Bagus Setiawan; Fuad Fauzi; Muhammad Dary Rafi; Edelweis Putri Prima; Baswara Yua Kristama (Prapanca : Jurnal Abdimas, 2024)
Tuberculosis (TB) is still a health and public health issue in Indonesia. TB can be treated and cured but remains a major killer infectious disease, leading to death. The approach is critical to finding, reaching and treating all people and communities affected by TB. Social and cultural factors greatly influence people’s TB risk and vulnerability, and their ability to access prevention. To socialize drug-resistant tuberculosis (TBRO) through various platforms, especially social media, Group 3 proposed Community services at Rekat Peduli Indonesia Foundation to assist and collaborate in fulfilling TBRO information content through the social media, especially Instagram. Our group will help create content on Rekat’s instagram, related to important information about TB disease.On the Field Study and Community Service carried out at the Rekat Peduli Indonesia Foundation, our group created content related to important information about TBRO, the release of pocket books latest and distribution of general brochures about TB to the public. With a schedule of 12 meetings, the activities we carry out include preparing a work program according to the needs of the Rekat Peduli Indonesia Foundation, creating content in the form of videos, finalizing content for the Foundation’s brochures and printing plans, distributing brochur